A chat-bot in rheumatoid arthritis treatment control - Yuliya A. Prokofeva; Elena A. Zheleznykh; Irina V. Menshikova (Digital Diagnostics, 2023)
BACKGROUND: Rheumatoid arthritis (RA) is an autoimmune rheumatic disease with joint damage and systemic manifestations, which worsens the quality of life and life expectancy, leading to disability in the absence of effective therapy at a young age. The goal of RA treatment is to achieve remission/low disease activity. Frequent monitoring of the disease is needed (every 13 months until the goal is reached, then every 36 months), which is not always possible due to remoteness of residence, financial capabilities of patients, and epidemic situation. Remote monitoring appears to be a possible solution to the problem; however, the effectiveness of telemedical technologies in the treatment of patients with RA is not sufficiently studied.